Heteromorphic Sex Chromosomes and Their DNA Content in Fish: An Insight through Satellite DNA Accumulation in Megaleporinus elongatus - Crepaldi, Carolina [UNESP]; Parise-Maltempi, Patricia P. [UNESP] (Karger, 2020)
The repetitive DNA content of fish sex chromosomes provides valuable insights into specificities and patterns of their genetic sex determination systems. In this study, we revealed the genomic satellite DNA (satDNA) content of Megaleporinuselongatus, a Neotropical fish species with Z(1)Z(1)Z(2)Z(2)/Z(1)W(1)Z(2)W(2) multiple sex chromosomes, through high-throughput analysis and graph-based clustering, isolating 68 satDNA families. By physically mapping these sequences in female metaphases, we discovered 15 of the most abundant satDNAs clustered in its chromosomes, 9 of which were found exclusively in the highly heterochromatic W-1. This heteromorphic sex chromosome showed the highest amount of satDNA accumulations in this species. The second most abundant family, MelSat02-26, shared FISH signals with the NOR-bearing pair in similar patterns and is linked to the multiple sex chromosome system. Our results demonstrate the diverse satDNA content in M. elongatus, especially in its heteromorphic sex chromosome. Additionally, we highlighted the different accumulation patterns and distribution of these sequences across species by physically mapping these satDNAs in other Anostomidae, Megaleporinusmacrocephalus and Leporinusfriderici (a species without differentiated sex chromosomes).
Keywords: FISH; Heteromorphic sex chromosome system; Neotropical fish; Satellitome; Sex chromosome evolution